2019
DOI: 10.1002/jcsm.12449
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia induces morphological and inflammatory changes in the intestinal mucosa

Abstract: BackgroundCachexia is a multifactorial and multiorgan syndrome associated with cancer and other chronic diseases and characterized by severe involuntary body weight loss, disrupted metabolism, inflammation, anorexia, fatigue, and diminished quality of life. This syndrome affects around 50% of patients with colon cancer and is directly responsible for the death of at least 20% of all cancer patients. Systemic inflammation has been recently proposed to underline most of cachexia‐related symptoms. Nevertheless, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 50 publications
(98 reference statements)
2
39
0
Order By: Relevance
“…The PNI, which is the nutritional index calculated using the peripheral lymphocyte count and the serum albumin level, was reported to be associated with the survival of CRC patients 21 . The GPS has been used in several different oncological field and could, due to the routine assessment of albumin and CRP, be assessed in all aspects of the prospective care of patients with cancer 22,23 . In the present study, although the PNI and the CONUT score were found to be predictive factors for RFS and OS in the univariate analyses, the results of the multivariate analysis demonstrated that only the CONUT score was an independent prognostic factor for these patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The PNI, which is the nutritional index calculated using the peripheral lymphocyte count and the serum albumin level, was reported to be associated with the survival of CRC patients 21 . The GPS has been used in several different oncological field and could, due to the routine assessment of albumin and CRP, be assessed in all aspects of the prospective care of patients with cancer 22,23 . In the present study, although the PNI and the CONUT score were found to be predictive factors for RFS and OS in the univariate analyses, the results of the multivariate analysis demonstrated that only the CONUT score was an independent prognostic factor for these patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The same cytokines together with the receptor activator of nuclear factor kappa-Β ligand (RANKL) can induce bone loss by apoptosis of osteoblasts and the differentiation of osteoclast precursor cells (OCPs) into activated bone resorbing cells [ 47 ]. Immune cell infiltration and other inflammatory changes can perturbate the intestinal microbiota composition and exacerbate mucosal damage and gut permeability [ 48 ]. Studies on murine models of cancer cachexia have demonstrated that neutrophils infiltration and microglia activation can contribute to brain dysfunction, probably through affecting sympathoexcitatory and anorexigenic neurons [ 49 , 50 ].…”
Section: Immune Systemmentioning
confidence: 99%
“…Whether these observations are clinically relevant remains to be determined. Interestingly, Costa et al reported morphological and inflammatory changes in the intestinal mucosa in healthy tissues of cachectic colon cancer patients compared to weight-stable colon cancer patients [ 48 ]. A full characterization of the gut microbiota of leukemia patients with and without cachexia is currently ongoing in an academic multi-centric prospective study (NCT03881826) and it should bring more light on this topic.…”
Section: Alterations Of the Intestinal Barrier And The Gut Microbimentioning
confidence: 99%
“…Beyond the well-characterized muscle–liver–adipose tissue axis, newly emerging evidence of possible interactions between skeletal muscle and the gut microbiota, the composition of which appears to be strongly influenced by physical activity and general performance status, suggests they may play a role in muscle wasting associated with diabetes, frailty, sarcopenia, and other cachectic conditions [ 108 ]. In aging subjects, as well as in patients with anorexia nervosa and in sedentary versus trained, shifts in the microbiota toward a less diversified composition have been correlated with decreased muscle function [ 109 ].…”
Section: Crosstalk Between Skeletal Muscle and Other Organs In Cacmentioning
confidence: 99%